Transport and fluctuations in nonlinear-dissipative systems: role of interparticle collisions - Katilius, R.; Matulionis, A.; Raguotis, R.; Matulionienė, I. (Nonlinear Analysis: Modelling and Control, 1999)
The goal of the paper is to overview contemporary theoretical and experimental research of the microwave electric noise and fluctuations of hot carriers in semiconductors, revealing sensitivity of the noise spectra to non-linearity in the applied electric field strength and, especially, in the carrier density. During the last years, investigation of electronic noise and electron diffusion phenomena in doped semiconductors was in a rapid progress. By combining analytic and Monte Carlo methods as well as the available experimental results on noise, it became possible to obtain the electron diffusion coefficients in the range of electric fields where inter-electron collisions are important and Price’s relation is not necessarily valid. Correspondingly, a special attention to the role of inter-electron collisions and of the non-linearity in the carrier density while shaping electric noise and diffusion phenomena in the non-equilibrium states will be paid. The basic and up-to-date information will be presented on methods and advances in this contemporary field - the field in which methods of non-linear analytic and computational analysis are indispensable while seeking coherent understanding and interpretation of experimental results.